Efficacy and safety of pseudolaric acid B against Echinococcus multilocularis in vitro and in a murine infection model - Dawa, Zhuo-ma; Zhai, Ting; Liu, Chuan-chuan; Fan, Hai-ning (Frontiers in Medicine, 2025)
IntroductionAlveolar echinococcosis (AE) is a chronic zoonotic disease caused by the larvae of the Echinococcus multilocularis (E. multilocularis). The current chemotherapy for AE relies on albendazole and mebendazole, which exhibit only parasitostatic rather than parasiticidal effects. Therefore, there is a need to find new anti-Echinococcosis drugs. Pseudolaric acid B (PAB) has been described to have strong antiparasitic effects. However, the in-depth mechanism by which PAB acts against E. multilocularis remains unclear.MethodsTo evaluate the effect of a PAB intervention on protoscoleces, metacestode vesicles and germinal cells in E. multilocularis in vitro. In addition, the effects of PAB on T lymphocyte and collagen synthesis were evaluated after PAB administration in a mouse model.ResultsMetacestode vesicles and germinal cells were successfully cultured, and specific genes were amplified via RT-PCR to identify the protoscoleces, vesicles, and germinal cells as the sources of E. multilocularis. In vitro studies have demonstrated that PAB exhibits dose- and concentration-dependent cytotoxicity against E. multilocularis protoscoleces. Scanning electron microscopy revealed that the microvilli structure of the protoscolex was destroyed and the rostellar hooks had fallen off. PAB induced. The release of PGI from the metacestode vesicles, leading to the structural destruction of the inner surfaces. PAB suppressed the proliferation of germinal cells. After PAB treatment, the serum and the host tissue surrounding the metacestodes IFN-γ levels were upregulated and the IL-4 and IL-10 levels was downregulated. After PAB treatment, the levels of CD4+ T lymphocytes increased and the levels of CD8+ T lymphocytes decreased in the host tissue surrounding the metacestodes and the spleen. The proportions of the Th1 and Th17 cell subpopulations were increased and the proportion of Th2 cell and Treg cell subpopulations was decreased in the host tissue surrounding the metacestodes. Additionally, collagen deposition was increased after PAB treatment. PAB suppressed the expression of matrix metalloproteinases (MMPs 1, 2, 3, 9, 13) and the activation of the PI3K/AKT signaling pathway in the host tissue surrounding the metacestodes.ConclusionPAB has a significant killing effect on E. multilocularis, suggesting that it is a potential candidate for the treatment of AE.